The development of the patient privacy scale in nursing - ÖZÇELİK, SEMANUR KUMRAL (SAGE PUBLICATIONS LTD, 2014)
Background: The developments in technology and communication channels, increasing workload, and carelessness cause problems regarding patient privacy and confidentiality in nursing services. Research objectives: The study was conducted to develop a patient privacy scale to identify whether nurses observe or violate patient privacy at workplace. Research design: This research was a methodological and descriptive study. Participants and research context: Participants were 354 nurses working at private hospitals and hospitals affiliated with the Ministry of Health in Istanbul/Turkey. Data were collected with a questionnaire about the demographic characteristics of nurses and their opinions about patient privacy and with patient privacy scale. Ethical considerations: After getting permission from the top management of hospitals, information about the study was given to nurses. Those willing to participate were informed that participation was voluntary and invited to give written consent before data collection. Findings: The content validity index of scale was 0.91, Cronbach's alpha was 0.93, Spearman-Brown and Guttman coefficients were 0.85, the upper and lower 27% test was -29.65, and item-total correlation values ranged from 0.47 to 0.71. The scale had five subscales. In addition, 49% of the nurses stated that patient privacy was always observed in their services/units. They appraised with a mean score of 4.51 +/- 0.49 for the total scale, 4.39 +/- 0.61 for confidentiality of personal information and private life, 4.39 +/- 0.70 for sexual privacy, 4.56 +/- 0.57 for the privacy of those unable to protect themselves, 4.60 +/- 0.59 for physical privacy, and 4.60 +/- 0.52 for ensuring a favorable environment. Discussion: The findings of this study were in contrast with the results of some international studies which determined the violation of the patient privacy. Conclusion: The patient privacy scale is a valid and reliable tool to collect data on whether nurses observe or violate patient privacy, and the nurses generally reported observing or paying attention to patient privacy in all hospitals and especially private hospitals.
Keywords: Hospital; nurse; nursing; patient; privacy; scale; EMERGENCY-DEPARTMENT; ELDERLY-PEOPLE; PERCEPTIONS; CARE